The dependence of the adaptation of the cardiovascular system in adolescents on the state of some environmental factors - Diana Koshkodan; Lora Moshanu-Shupac (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii, 2024)
This article presents the experimental data related to the ecological factors that have an impact on the adaptation of children and adolescents. The selected ecological factors are the air and water quality in the areas surrounding the investigated educational institutions. It was established that there is a correlation between the degree of pollution of the external environment and the cardiovascular indices of adolescents. Thus, for the students from the academic institutions located in the more polluted areas, the indices of heart economy and the restoration of the frequency of heart contractions after physical effort are lower compared to those of students located in the educational institutions from the less polluted areas.